Análisis de productos para prevenir autolesiones en niños con síndrome de Down de grado moderado. - Toapanta Nuela, Bryan José (2025)
Down syndrome is a genetic condition caused by the trisomy of chromosome 21, which leads to various physical and intellectual challenges. This highlights the need to develop adapted products that promote both safety and well-being for children. The research evaluates the impact of sensory and immobilizing toys on improving the safety and well-being of this population. Using methodologies such as Design Thinking and User-Centered Design (UCD), the goal is to design ergonomic and safe products specifically tailored to meet the needs of these children. This thesis aims to analyze products that prevent self-harm in children with moderate Down syndrome to improve their safety and protection, contributing to their specific needs in the context of specialized educational centers. A design brief provides designers with a practical guide for developing these products. The study includes a review of safe materials and sensory elements that enhance cognitive and emotional development. Additionally, a triangulation of data from interviews with educators and caregivers is conducted, validating the effectiveness of existing products and proposing improvements based on concrete experiences and identified needs. The thesis emphasizes the importance of creating comprehensive solutions that not only mitigate physical risks but also promote an enriching environment for the holistic development of children. The findings highlight the importance of providing solutions that, in addition to preventing physical harm, contribute to the overall well-being and improve the quality of life for children with Down syndrome. These findings underscore the essential role that well-designed products play in supporting their growth and development.